Effectiveness of single-dose azithromycin to treat latent yaws: a longitudinal comparative cohort study - Oriol Mitjà, DrMD; Camila González-Beiras, BSc; Charmie Godornes, BSc; Reman Kolmau, BSc; Wendy Houinei, HEO; Haina Abel, BSc; August Kapa, BSc; Raymond Paru, BSc; Sibauk V Bieb, MaHM; James Wangi, MPH; Sergi Sanz, MSc; Kingsley Asiedu, MPH; et al. (Elsevier, 2017)
Summary: Background: Treatment of latent yaws is a crucial component of the WHO yaws eradication strategy to prevent relapse and the resulting transmission to uninfected children. We assessed the effectiveness of single-dose azithromycin to treat patients with latent yaws. Methods: This population-based cohort study included children (age <20 years) living on Lihir Island, Papua New Guinea, with high-titre (rapid plasma reagin titre ≥1:8) latent or active yaws, between April, 2013, and May, 2015. Latent yaws was defined as lack of suspicious skin lesions or presence of ulcers negative for Treponema pallidum subsp pertenue on PCR, and active yaws was defined as ulcers positive for T pertenue on PCR. All children received one oral dose of 30 mg/kg azithromycin. The primary endpoint was serological cure, defined as a two-dilution decrease in rapid plasma reagin titre by 24 months after treatment. Treatment of latent yaws was taken to be non-inferior to that of active yaws if the lower limit of the two-sided 95% CI for the difference in rates was higher than or equal to −10%. This study is registered with ClinicalTrials.gov, number NCT01955252. Findings: Of 311 participants enrolled, 273 (88%; 165 with latent yaws and 108 with active yaws) completed follow-up. The primary endpoint was achieved in 151 (92%) participants with latent yaws and 101 (94%) with active yaws (risk difference −2·0%, 95% CI −8·3 to 4·3), meeting the prespecified criteria for non-inferiority. Interpretation: On the basis of decline in serological titre, oral single-dose azithromycin was effective in participants with latent yaws. This finding supports the WHO strategy for the eradication of yaws based on mass administration of the entire endemic community irrespective of clinical status. Funding: Newcrest Mining Limited and ISDIN laboratories.